1976
DOI: 10.1128/aac.9.5.804
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Direct and Standardized Disk Diffusion Susceptibility Testing of Urine Cultures

Abstract: A comparison between direct and standardized disk diffusion tests was made on a total of 300 urine specimens containing 105 organisms/ml. Of these, 246 represented pure cultures and 54 represented mixed cultures. The number of major discrepancies per organism tested in pure culture was 18 (7.3%) and in mixed cultures it was 23 (42.6%). The percentage of major discrepancies per total number of antimicrobial drug comparisons made was 1.4%. Although this procedure may be of value in selected cases with pure cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…The results in our study show close cor respondence with the report by Hollick and Washington [1976], who found 95.5% con cordance, and by Perez and Gillenwater [1973], whose figure was 96.8%. Perez and Gillenwater concluded that direct testing is of great value in clinical practice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results in our study show close cor respondence with the report by Hollick and Washington [1976], who found 95.5% con cordance, and by Perez and Gillenwater [1973], whose figure was 96.8%. Perez and Gillenwater concluded that direct testing is of great value in clinical practice.…”
Section: Discussionsupporting
confidence: 81%
“…As a rule these tests are based on a disc diffusion procedure with standardized inoculum. The direct disc diffusion method, be used in a clinical microbiological without standardized inoculum, has been evaluated in clinical practice [Perez and Gillenwater, 1973;Hollick and Washington, 1976;Dornbusch et al, 1979], with con flicting judgements concerning its usefulness in routine work. The purpose of the present study, therefore, was to evaluate the results of direct susceptibility tests further by com parisons with standardized tests on urine cultures in a clinical laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in our laboratory comparing direct and standardized disk diffusion susceptibility tests on urine specimens produced results similar to those obtained in this study (5).…”
Section: Methodsmentioning
confidence: 42%
“…However, clinicians still ponder in disbelief when an oral antibiotic, e.g., doxycycline is used for formidable uropathogen, e.g., P. aeruginosa. Because tetracyclines are not routinely tested against Gram negative uropathogens many physicians do not even consider doxycycline a therapeutic option [11,12,17,18,20]. I continue to use oral antibiotics successfully based on the estimated urinary concentrations to eliminate a variety of aerobic Gram negative uropathogens from bladder urine.…”
mentioning
confidence: 99%
“…Clinicians often forget that in vitro susceptibility testing is based on achievable serum concentrations for rapidly growing aerobic organisms and primarily pertains to bloodstream infections. In vitro susceptibility testing, by definition, is at best an extrapolation of conditions at the site of infection, i.e., with lower UTIs since susceptibility testing is performed in broth (not serum), at serum pH07.4 (not urinary pH) and at 35°C (not body temperature) [19,20]. For lower tract UTIs, some have tried to more closely predict in vivo effectiveness by performing susceptibility tests on Gram negative uropathogens in human urine, at urinary pH, and at achievable urinary concentrations (Table 3) [21].…”
mentioning
confidence: 99%